PEMANFAATAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN MELALUI PROGRAM WIRAUSAHA MERDEKA UNIVERSITAS MUHAMMADIYAH SURAKARTA 2023 - Pramita Devi Mutia Syarifah; Shinta Permata Sari (LPPM ITB AAS Indonesia Surakarta, 2024)
Entrepreneurship has an important role in the economic growth of a country. Universitas Muhammadiyah Surakarta’ Independent Entrepreneurship Program is one of the programs organized by the government with the hope of being able to help the growth of Micro, Small and Medium Enterprises in Indonesia, especially the Natureline business. Natureline has problems related to instability in product sales. This Independent Entrepreneurship Program activity aims to find out the stages of effective use of digital marketing in purchasing decisions. The method developed in this activity is through the preparation stage, implementation stage and evaluation stage. The preparation stage is the interview activity and determining the target market, the implementation stage is the digital platform identification stage, and the evaluation stage is the digital platform development and promotion stage. The results of this activity are the development of digital platforms in the form of social media and marketplaces as well as the development of Natureline business promotions. Through the Independent Entrepreneurship Program, it turns out that it can provide solutions to partner problems which are expected to contribute to sales of Natureline products and improve purchasing decisions for customers and potential customers who buy Natureline products.